Studi Mekanisme Molekuler Antibakteri dari Daun Telang (Clitoria ternatea L.) - Mario Hendrik Refwalu; Ana Indrayati; Ika Purwidyaningrum (Jurnal Farmasi Indonesia, 2023)
The bacterium is one of the infectious pathogens that cause infectious diseases. A problem currently developing in the treatment of infectious diseases is antimicrobial resistance. Antimicrobial resistance is the inability of an antibiotic to cure infectious diseases so that new antimicrobial compounds are needed that can kill infectious pathogens (by bacteria, fungi, viruses, and multi-cellular parasites). The butterfly pea plant (Clitoria ternatea L.) has been identified as a potential antibacterial plant. This literature study aims to determine the antibacterial activity and identify molecular mechanisms based on the chemical content of telang leaves that have not been done before. This literature study uses the systematic literature review (SLR) method to determine the activity and antibacterial mechanisms based on the bioactive compounds contained by using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyzes) as the review protocol. Data search strategy using search engines: science direct, google scholar, and Pubmed. The keyword search uses a combination of words in the problem statement and uses the Boolean "OR" and "AND". The finding shows that the relevant literature obtained 22 articles that met the criteria consisting of articles on chemical compounds, antibacterial activities and mechanisms. The SLR results showed that telang leaf has potential as an antibacterial and has a molecular mechanism, namely, interfering with the permeability of cell membranes, inhibiting nucleic acid and protein synthesis and inhibiting the formation of biofilms. Chemical compounds that have the potential as antibacterial agents are kaempferol, quercetin, cyclotide, b-sitosterol alkaloids and tannins.